Resilience in Crimea: the history of the Crimean Tatars - Kachmarsky, Avery J. (Young Scholars Grinchenko – Seton International Journal, 2025)
This essay explores the history of the Crimean Tatars, from their origins as a Turkic-speaking people in medieval Crimea to their significant political and cultural role under the Crimean Khanate. The impact of Russian imperialism, Soviet repression, forced deportation in 1944, and struggles faced upon their return to Crimea after the collapse of the Soviet Union are examined. The ongoing persecution of the Crimean Tatar community following Russia’s illegal annexation of Crimea in 2014 is also discussed, highlighting their resistance to occupation amidst efforts to suppress their language, culture, and political representation. This examination of the ongoing oppression and challenges faced by the Crimean Tatars sheds light on their resilience and the enduring spirit of their proud heritage.